Violence against health care workers in rural areas of Sindh, Pakistan - Arif, Saleema; Baig, Lubna Ansari; Shaikh, Shiraz; Hashmi, Ibrahim; Sarwar, Zaini; Baig, Zarrukh Ali (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the magnitude of violence against healthcare workers in a rural setting, and the consequences of this violence on their personal and professional lives. Method: The descriptive, quantitative, cross-sectional study was conducted in 4 rural districts of the Sindh province of Pakistan from February to December 2019, and comprised healthcare workers, including doctors, nurses, support staff and field workers. Data was collected using a structured questionnaire. Data was analysed using SPSS 22 Results: Of the 1622 subjects, 929(57.3%) were males and 693(42.7%) were females. The overall mean age was 35.55+/-10.05 years. The largest cluster was that of doctors 396(24.4%), followed by technicians 202(12.5%). Overall, 522(32.2%) subjects had a professional experience of 1-5 years. Violence at workplace in any form was experienced by 693(42.7%) subjects. Verbal violence had been experienced by 396(24.4%) subjects, while 228(14.1%) had witnessed it. The corresponding numbers for physical violence were 122(7.5%) and 22(1.4%). Verbal violence was more prevalent compared to physical violence (p<0.01). The major effect was that the healthcare workers remained alert 537(33.1%), felt frustrated 524(32.3%) and disturbed 503(31%). Also, 272(16.8%) subjects were planning to migrate or quit the profession. Conclusion: Violence was found to be a significant issue in rural Sindh. Key Words: Violence, Healthcare, Danger, Rural, Pakistan, Sindh.